Rancang Bangun Aplikasi Kelayakan Pemberian Kredit dan Pencatatan Pembayaran Kredit pada Koperasi Serba Usaha Mitra - Kaisha Satrio Noor Hutomo; Tutut Wurijanto; Vivine Nurcahyawati (Jurnal Sistem Informasi Universitas Dinamika, 2017)
Koperasi Serba Usaha (KSU) Mitra is a cooperative that located at Genteng, Banyuwangi. KSU Mitra have a loan services products to their member. KSU Mitra using the principles of 5C assessment to assess worthiness of the loan application. The existing conditions, the principle of 5C assessment not fully performed. This led to the credit risk on loans granted. This occurs because the assessment process is not recorded. And the recording of loan payments still recorded in simple manner. To resolve the issue then assessment worthiness of loan giving and loan payments recording is made. Applications are made to assess the worthiness of loan giving based on the principles of 5C and can handle the recording of loan payments. Based on trial results that have been done, can be concluded that this application complies with the expected goals. This application has been able to assess the worthiness of loan giving based on the principles of 5C assessment and recorded the loan payments on KSU Mitra.